The Economic Effects of Genocide: Evidence from Rwanda†. (22nd May 2018) - Hodler, Roland
Abstract: Cross-country studies on the economic consequences of internal political violence typically find short-run effects that are not very large, and no evidence for full economic recovery. We study the economic impact of the Rwandan genocide in 1994, which has been one of the most intense events of political violence since World War II. More precisely, we estimate its effect on economic development using the synthetic control method and addressing data quality issues that have been a concern in the literature. We find a 58% decrease in GDP in 1994. This effect still corresponds to a decrease in GDP per capita of around 31% when taking into account that 800, 000 people were killed and that around two million fled the country during the genocide. We further provide strong evidence that Rwanda's economy was then catching up with the estimated counterfactual GDP it would have had in absence of the genocide, with the gap closing after 17 years. When focusing on the effects on the Rwandan exports as reported by the importing countries, we find similar short-run effects but somewhat slower recovery. We finally show that agriculture was less severely hit by the genocide than the industry and service sectors, and that it also recovered much more quickly.